1999
DOI: 10.1177/00912709922008434
|View full text |Cite
|
Sign up to set email alerts
|

Montelukast Dose Selection in 6‐ to 14‐Year‐Olds: Comparison of Single‐Dose Pharmacokinetics in Children and Adults

Abstract: Montelukast, an oral leukotriene-receptor antagonist, has demonstrated efficacy and tolerability for the treatment of chronic asthma in adults. A once-daily 10 mg dose (film-coated tablet) was selected as the optimal adult dose based on dose-ranging studies. Asthma is a similar disease and is treated with the same medications in children and adults. These observations suggested that a dose of montelukast in children providing overall drug exposure (i.e., montelukast plasma concentrations) similar to that of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
61
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 45 publications
(66 citation statements)
references
References 21 publications
5
61
0
Order By: Relevance
“…The steady-state volume of distribution and clearance in a 70-kg adult were estimated to be 8.2 L and 43 ml/min, respectively, which is consistent with published results that use traditional noncompartmental analysis (13). Previous studies after oral administration of montelukast have indicated that the pharmacokinetic profiles of montelukast are different in adults and children (23). Consistent with those observations, we observed dissimilar pharmacokinetics after intravenous administration between the two populations that we studied.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…The steady-state volume of distribution and clearance in a 70-kg adult were estimated to be 8.2 L and 43 ml/min, respectively, which is consistent with published results that use traditional noncompartmental analysis (13). Previous studies after oral administration of montelukast have indicated that the pharmacokinetic profiles of montelukast are different in adults and children (23). Consistent with those observations, we observed dissimilar pharmacokinetics after intravenous administration between the two populations that we studied.…”
Section: Discussionsupporting
confidence: 90%
“…A 10-mg film-coated tablet in adults, a 5-mg chewable tablet in children aged 6 to 14 years, and a 4-mg chewable tablet or oral granules in children aged 2 to 5 years are approved for use in the clinic. These oral doses yield similar systemic exposures that are also associated with efficacy in the respective age groups (15,17,23). In adult patients with chronic asthma, a single 7-mg intravenous dose was found to be as effective as a 10-mg oral dose of montelukast (31).…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…34 Yet another study indicated that a 5 mg chewable tablet administered once daily to children aged 6-14 years with asthma, resulted in a pharmacokinetic profile comparable to that of the clinically effective 10 mg FCT dose in adults. 35 …”
Section: Plasma Concentrations In Adults and Childrenmentioning
confidence: 99%